A Review on Scope of 3D Palm Print and Its Application in Modern ERA: Advancements and Applications of 3D Palm Print Biometrics (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Biometrics is technology of identifying uniquely human subjects by means of measuring analyzing one or more inherent behavioral or physical traits. These human body characteristics include fingerprints, voice patterns, eye retinas irises, facial patterns hand dimension. Biometric systems are used to authenticate identity by measuring physiological andor behavioral characteristics. So, two main categories of biometrics are ‘physiological’ andor ‘behavioral’. The physiological category includes physical human traits such as palm print, hand shape, eyes, veins, etc. The behavioral category includes movement of human, such as hand gesture, speaking style, signature etc. The measurement of these traits helps within authentication using biometric systems. In this paper the study has been made about existing biometric system along with their working and application in modern era. This paper also represents various researches in field of 3D PALM PRINT.